Synthesis of Metal-Organic Frameworks containing Heterocyclic Linkers for application in CO2 storage/utilization and Luminescent Sensing - MERCURI, GIORGIO (Università degli Studi di Camerino, 2023)
Metal-organic frameworks (MOFs) are hybrid organic/inorganic 3D coordination polymers with open structures deriving from the self-assembly of polytopic linkers and metal ions or metal- based clusters. In more recent years, MOFs have emerged as promising alternative to all- inorganic materials (e.g. activated carbons and zeolites) in industrially and technologically relevant applications requiring porous compounds, such as gas adsorption or separation, heterogeneous catalysis and luminescence sensing. The tailored design of polydentate linkers (carboxylates, azolates) for MOFs construction is of fundamental importance to prepare well- performing materials for a target application. At present, a wide plethora of organic spacers has been prepared for this task. In many cases, the building units exploited are rigid aromatic six- membered fully carbocyclic rings (isolated or conjugated: benzene, 4,4'-biphenyl, terphenyl, naphthalene, anthracene, pyrene) decorated with carboxylate groups as coordinating units to metal centers. The introduction of heteroatoms or tailored functional groups within the linkers skeleton is generally beneficial to improve the MOF performance in a given process like gas adsorption/separation/transformation. One important example belonging to this category is that of carbon dioxide. The steadily increasing atmospheric concentration of carbon dioxide and the consequences of this phenomenon in terms of Earth’s global warming (the so-called greenhouse effect), ocean acidification, melting of polar ices and rising sea level are of primary concern for the scientific community. Carbon capture and storage (CCS) is a modern approach to solve this problem. CCS technologies based on CO2 adsorption by nano-porous adsorbents have become popular. MOFs have gained great attention in this context. The extraordinary versatility in MOFs design is the main reason for their applicative success. MOFs hold unique advantages, including control of their pore size and shape, high specific surface area, and the ...